Covalent organic framework membrane for size selective release of small molecules and peptide in vitro. Issue 35 (26th August 2020) - Rezvani Alanagh, Hamideh; Rostami, Iman; Taleb, Mohammad; Gao, Xiaoqing; Zhang, Yadong; Khattak, Abdul Muqsit; He, Xiao; Li, Lianshan; Tang, Zhiyong
Abstract : The ability to control small drug release is crucial in biomedicine, especially for inhibiting the side effects of drugs, but it is still challenging. Abstract : The ability to control small drug release is crucial in biomedicine, especially for inhibiting the side effects of drugs, but it is still challenging. Herein, to mimic the controlled release of drugs, the release of organic molecules, e.g., small organic dyes and peptides, through Covalent Organic Framework (COF) membranes with ordered nanoscale pores has been investigated, showing constant zero-order release behaviours. Meanwhile, biological assessments show the good biocompatibility of the COF membrane-based release system, and the high stability of the COF membrane was manifested by the long-term release of small molecules in aqueous media.